2015
DOI: 10.21664/2238-8869.2015v4i3.p219-230
|View full text |Cite
|
Sign up to set email alerts
|

Novas Fronteiras no Oeste: Relação entre sociedade e natureza na microrregião de Ceres em Goiás (1940-2013)

Abstract: Esta nota científica visa apresentar o projeto de pesquisa em andamento resultante da parceria e cooperação interinstitucional dos docentes dos Programas de Pós-Graduação em Geografia, da Universidade Estadual Paulista “Júlio Mesquita Filho” – Campus Presidente Prudente (PPGG/UNESP); em Sociedade, Tecnologia e Meio Ambiente do Centro Universitário de Anápolis (PPSTMA/UniEVANGÉLICA); e em Desenvolvimento Sustentável da Universidade de Brasília (CDS/UnB) de acordo com os objetivos do Programa Nacional de Coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…For the 1,182.22 km2 of APPs delimited by watercourses and tops of hills and slopes, 795.61 km2 have native vegetation and 386.61 km2 are in an inadequate situation, that is, they are mainly using livestock (276, 11 km2), followed by sugar cane (88.08 km2) and agriculture (65.32 km2). Similar results were found by Ferreira (2015), in a study carried out in the municipality of Carmo do Rio Verde, revealing that pasture occupies the largest area of APPs in the area of the Rio das Almas watershed. Garcia et al (2015) observed the same situation in the Barra Seca stream watershed (Pedreiras / SP) and Soares et al (2011) in the São Bartolomeu river basin (MG).…”
Section: Results E Discussionsupporting
confidence: 85%
“…For the 1,182.22 km2 of APPs delimited by watercourses and tops of hills and slopes, 795.61 km2 have native vegetation and 386.61 km2 are in an inadequate situation, that is, they are mainly using livestock (276, 11 km2), followed by sugar cane (88.08 km2) and agriculture (65.32 km2). Similar results were found by Ferreira (2015), in a study carried out in the municipality of Carmo do Rio Verde, revealing that pasture occupies the largest area of APPs in the area of the Rio das Almas watershed. Garcia et al (2015) observed the same situation in the Barra Seca stream watershed (Pedreiras / SP) and Soares et al (2011) in the São Bartolomeu river basin (MG).…”
Section: Results E Discussionsupporting
confidence: 85%
“…The first record referring to MGG in official documents was a request to the King [D. José] by Bento Colaço de Morais, dated February 28, 1769, requesting confirmation of the land title for a site identified as "Edge of Mato Grosso, old village road that begins, on the Northern band, with D. Margarida da Silva,captainship of Goiás". 1 The deforestation of the MGG region resulted from several territorial occupations and land use policies in Goiás during the first half of the 20th century, in association with the historic deforestation of the Brazilian tropical forest for agricultural use (JAMES, 1953;DEAN, 1995LEAL et al, 2015). In the MGG region, deforestation was accompanied by the expansion of coffee production into the western region of São Paulo during the initial decades of the 20th century and the search for forested areas for expansion of agricultural activities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the historical geography and environmental history of the MGG reveal that the criteria for the choice and construction of Brasília, the new Brazilian capital, favoured areas with considerable forest density that could serve as an agricultural reserve for the population that would migrate into the region. Among the tropical forest areas, the largest area (approximately 20,000 km2) with appropriately fertile soil was the MGG, which in 1947-at the time of the expedition for the selection of the new federal capital-was experiencing intense migration (JAMES and FAISSOL, 1960;DUTRA E SILVA et. al, 2015; DUTRA E SILVA, 2017).…”
Section: Introductionmentioning
confidence: 99%